2011
DOI: 10.15241/mpa.1.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Graduate Students’ Statistics Self-Efficacy, Statistics Anxiety, Attitude Toward Statistics, and Social Support

Abstract: Aligning with a particular theoretical orientation or personal multi-theory integration is often a formidable task to entry-level counselors. A better understanding of how personal strengths and abilities fit with theoretical approaches may facilitate this process. To examine this connection, thirty-five mental health professionals completed a series of inventories to determine if passive counselors adhere to more nondirective, insight-oriented theories, while assertive counselors adhere to more directive, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
49
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 30 publications
(1 reference statement)
14
49
0
1
Order By: Relevance
“…There is a consistent negative relationship reported between statistics anxiety and course performance (Onwuegbuzie & Wilson, 2003), and evidence of a positive relationship between self-efficacy and performance (Lane, Hall, & Lane, 2004). Our finding of a strong negative relationship between anxiety and self-efficacy supports past findings (Onwuegbuzie, 2000;Pajares & Miller, 1995), and it has been suggested that poor self-efficacy beliefs in the face of learning statistics may create a selffulfilling prophecy for students (Perepiczka, Chandler, Becerra, 2011).…”
Section: Resultssupporting
confidence: 86%
“…There is a consistent negative relationship reported between statistics anxiety and course performance (Onwuegbuzie & Wilson, 2003), and evidence of a positive relationship between self-efficacy and performance (Lane, Hall, & Lane, 2004). Our finding of a strong negative relationship between anxiety and self-efficacy supports past findings (Onwuegbuzie, 2000;Pajares & Miller, 1995), and it has been suggested that poor self-efficacy beliefs in the face of learning statistics may create a selffulfilling prophecy for students (Perepiczka, Chandler, Becerra, 2011).…”
Section: Resultssupporting
confidence: 86%
“…Liu, Onwuegbuzie&Meng (2012) using samples size of 201 college students in china found that students experiences statistics anxiety this is also consistent with the findings of Perepiczka et al (2011).…”
Section: Discussionsupporting
confidence: 66%
“…Viewing along the same line, Kpolovie (2010) asserts that conducting of a research is a sine qua non for graduation, be it for first degree, masters or doctoral level. Statistics courses are key requirement for many university programmes (McGrath et al, 2015;Onwuegbuzie& Wilson, 2003;Perepiczka et al 2011). These courses help students learn the skills necessary to conduct their own research to interpret and critically evaluate real world concepts.…”
Section: Introductionmentioning
confidence: 99%
“…This rating provides students with increased self-efficacy especially in discrete mathematics courses. self efficacy is one of the important factors in learning mathematics [4], because the passion of learning can improve learning outcomes [5] …”
Section: Introductionmentioning
confidence: 99%